Internet of Things: Spectral Demand in Mexico - Ruíz, José Luis Cuevas (Law, State and Telecommunications Review, 2019)
Purpose ”“ The present text seeks to examine the amount of spectrum to be used, mainly due to the scarcity and costs of the same, for the implementation of IoT services with high demand, based on the conditions of Mexico. Methodology/approach/design ”“ The present study will analyze the conditions of bandwidth demand and connection speeds for certain IoT applications. For the calculation of the bandwidth, the procedure used to obtain the bandwidth requirements considering different work cycles for various IoT applications is applied; This procedure has been applied for the estimation of the bandwidth in smart cities in India. The procedure makes use of population data to determine the current and potential density of IoT devices connected through wireless networks; At the same time, an area of coverage of the network is calculated, considering the typical radio coverage for urban, semi-urban and rural areas. With the above data, it is possible to obtain the number of devices in the coverage area of the network and with this the total traffic demand, to finally estimate the value of the bandwidth. Findings ”“ Considering the five regions with the highest population density, the amount of bandwidth was projected up to the year 2023. The spectral needs can vary considerably from one area to another. The results obtained present a direct dependence on the size of the cell to be considered. The radio coverage of the cell can vary depending on the type of geographical area, so that an increase of 1 km in the coverage radius could represent an increase of up to twice the spectrum demand.